Propuesta de un catálogo de tortas y bocaditos personalizados para el micro emprendimiento “Pequeños Caprichos” en Ibarra - Torres Moran, Alejandra Anahi (2024)
Gastronomy can be defined as a cultural expression or manifestation that reflects the identity and traditions of a community. In the Cantón Bolívar, Carchi, the local culinary richness is a treasure little known by both residents and visitors. This thesis focuses on the rescue and promotion of the Cantón Bolívar through its traditional gastronomy, in a digital medium, in order to position it as a renowned culinary and tourist destination. The main objective of the study is to value the traditional gastronomy of the Cantón Bolívar through the creation of attractive and accessible digital content. To achieve this objective, an inductive-deductive and analytical-synthetic methodology was adopted. Detailed observations of local culinary practices were made and community members were directly engaged to collect data on recipes, preparation techniques, and food preferences. This information was then analysed and visual digital content was created, including videos, photographs and informative articles. The results of the research reveal that the gastronomy of the Cantón Bolívar has enormous potential to be a significant tourist attraction. During the interviews, the traditional dish known as 'delicados' was highlighted, whose preparation is an 80-year-old tradition. One interviewee, a traditional chef, emphasized the importance of teaching these recipes to young people to prevent them from being lost, pointing out that the current versions are not the same as the traditional ones. The need for local support to preserve and promote these traditions, which have been internationally recognized, but lack incentive and support from the authorities, was also mentioned. In conclusion, the research contributes significantly to the rescue and dissemination of the canton Bolívar through its traditional gastronomy, in addition to offering an invaluable valuable resource that favors the economic and cultural progress of the sector